PENANGANAN ANAK ATTENTION DEFICIT HYPERACTIVITY DISORDER ( ADHD ) MELALUI TERAPI PERMAINAN PLAY-DOH DI PAUD KB SIMPATI KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR - Murty, May Marda (UNISAN JURNAL, 2025)
This article aims to understand the definition of ADHD, the causes of ADHD, the characteristics of ADHD, education for ADHD, and games for ADHD. ADHD is a neurodevelopmental disorder characterized by symptoms of inattention, hyperactivity, and clinical characteristics that can make it difficult for them to interact at home, school, work, and social settings. The causes of ADHD include genetics, parental dietary patterns during pregnancy, poor parenting, environmental factors such as lead poisoning, food addiction, and allergic reactions, which can lead to undesirable outcomes such as defiance or rule-breaking, difficulty socializing with others, lack of self-confidence, poor organizational skills, boredom, and anxiety. It is important for us to understand ADHD so we won’t be surprised if we encounter a child with ADHD